A novel "clip-and-link" activity of repeat in toxin (RTX) proteins from gram-negative pathogens. Covalent protein cross-linking by an Asp-Lys isopeptide bond upon calcium-dependent processing at an Asp-Pro bond - Osicka, Radim; Procházková, Katerina; Sulc, Miroslav; Linhartová, Irena; Havlícek, Vladimír; Sebo, Peter (The Journal of biological chemistry, 2004)
Clinical isolates of Neisseria meningitidis produce a repeat in toxin (RTX) protein, FrpC, of unknown biological activity. Here we show that physiological concentrations of calcium ions induce a novel type of autocatalytic cleavage of the peptide bond between residues Asp(414) and Pro(415) of FrpC that is insensitive to inhibitors of serine, cysteine, aspartate, and metalloproteases. Moreover, as a result of processing, the newly generated amino-terminal fragment of FrpC can be covalently linked to another protein molecule by a novel type of Asp-Lys isopeptide bond that forms between the carboxyl group of its carboxyl-terminal Asp(414) residue and the epsilon-amino group of an internal lysine of another FrpC molecule. Point substitutions of negatively charged residues possibly involved in calcium binding (D499K, D510A, D521K, and E532A) dramatically reduced the self-processing activity of FrpC. The segment necessary and sufficient for FrpC processing was localized by deletion mutagenesis within residues 400-657, and sequences homologous to this segment were identified in several other RTX proteins. The same type of calcium-dependent processing and cross-linking activity was observed also for the purified ApxIVA protein of Actinobacillus pleuropneumoniae. These results define a protein cleavage and cross-linking module of a new class of RTX proteins of Gram-negative pathogens of man, animals, and plants. In the calcium-rich environments colonized by these bacteria this novel activity is likely to be of biological importance.
Keywords: tosyllysinchlormethylketon; molekulová hmotnost; Calcium; Bacterial Proteins; Molecular Weight; vápník; membránové proteiny; Membrane Proteins; molekulární sekvence - údaje; Amino Acid Sequence; Gram-Negative Bacteria; tosylfenylalanylchlormethylketon; Cytotoxins; Tosylphenylalanyl Chloromethyl Ketone; Tosyllysine Chloromethyl Ketone; bakteriální proteiny; sekvence aminokyselin; Catalysis; gramnegativní bakterie; Molecular Sequence Data; katalýza; cytotoxiny